Health care seeking behavior among females in Pokhara: A case study - Rokaya, Raj Bahadur (Janaprakash Journal of Multidisciplinary Research, 2025)
Health care seeking behavior is the psychological behavior that a person and family search for the health care after the illness. The pathway model assumes that individuals have equal access to healthcare and can rationally evaluate their options. The objective of the study is to explore the health care seeking behavior of women in Pokhara, Kaski. The study carried out the qualitative research paradigm with case study research design. Primary qualitative data were collected from purposive sampling technique. Data were collected through an in depth interview guide and case study checklist developed in accordance with the Pathway Model of Health-Seeking Behavior and thematically analyzed using model-guided coding and cross-verification of narratives to enhance reliability. It is found that the case was aware of health illness. The case responded according to the intensity and time duration of the illness. Family members’ suggestions are main supportive factors for health service seeking behavior. There is not any practice of the home remedies and ayurvedic medicine or treatment system. Family members also took suggestion from other paramedics of the health personnel for the service seeking. findings indicate that female do not always follow the linear pathway assumed in conventional health-seeking models; instead, they often rely on informal care, normalize symptoms, and delay professional treatment even when health services are available. Although family support plays a positive role in encouraging care seeking, women’s decisions are strongly influenced by deeply rooted gender norms and personal expectations, particularly during midlife health transitions